PENGARUH MODEL INKUIRI TERBIMBING BERBANTUAN MEDIA FLIPBOOK TERHADAP HASIL BELAJAR SISWA MATERI IKATAN KIMIA - Louis Chris Manuel Zega; Dian Howan; Jakub Saddam Akbar; Angga Makarawung (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to identify the effect of a guided exploratory learning model using the “Flipbook” medium on student learning outcomes in the subject of chemical bonding. This study employs a quantitative approach using a quasi-experimental method and an unbalanced control group design. The sample consisted of two classes: the experimental group comprised 20 students and the control group comprised 21 students. The results of the study indicate that the average final exam score for the experimental group reached 79, which is higher than the control group’s average of 69. The hypothesis testing results showed a significance level of less than 0.05, indicating a statistically significant difference between the two classes. Furthermore, the N-Gain score for the experimental group reached 66%, which falls into the “moderate effectiveness” category, while the control group’s score of 42%falls into the “low effectiveness” category. From this, it can be concluded that the implementation of the guided exploratory learning model using animated picture books has a significant and effective impact on improving students’ learning outcomes in the subject of chemical bonding.